Mejoramiento y ampliación de los sistemas de agua potable y alcantarillado de la localidad de Nazareno-Ascope - Cordova Cordova, Joel Filemon (2016)
This project directed and accomplished on the improvement and enlargement of the drinkable- water and sewage system systems of Nazareno Ascope's locality, it allows giving a solution to drinkable and laid sewers in the deficiency of coverage of the water supply utilities, and most of all with the execution of this project get better notably the community's conditions of life and of health, infectocontagiosas that cause morbility and mortality that they affect the settlers due to the scarcity of this service will specifically reduce diseases themselves, likewise increment him the socioeconomic level of the settlers of the locality. Our planning is directed to a rural zone, with topography full of unforeseen obstacles. Himself to once the measurement of the water of the spring in period of avenues was accomplished, stepping down he is in time of low water and he has taken in account the hydraulic and structural calculation of every an one belonging to the civil works. At the drinkable- water supply system, use him 01 comprehension guy slope, lines of driving with pipes of PVC SAP C 10 for the nets of open distribution, 10 cameras the guy breaks off pressure 7 and 75 domiciliary stone basins; And for the system of sanitation 75 sanitary latrines will build for themselves guy dry airy hole. The water supply system is a system for gravity without treatment with a designing period of 20 years, and the system of basic sanitation is with sanitary latrines of dry processes with a designing period of 10 years